The rationale and application of eccentric-based exercises in sports: practical suggestions for its implementation - Beato, M.; Hughes, J.; Taber, C.; Baumert, P.; Suchomel, T. J. (Strength and Conditioning Journal, 2025)
Considering the great popularity of eccentric-based training, the purpose of this review is to first provide the scientific rationale for its use; second, summarize the eccentric-based training modalities that can be used; and finally, offer practical recommendations on how to implement eccentric-based modalities to enhance sports performance. The molecular and neural mechanisms underlying eccentric actions are partially distinct from those of concentric and isometric actions. During eccentric actions, theories suggest a strain-induced modulation of actin-myosin interactions at the cross-bridge level, activation of structural protein titin, and winding of titin on actin. Eccentric acute physiological responses differ from concentric exercise responses, including variations in neuromuscular, metabolic, hormonal, and anabolic signaling. Eccentric training elicits greater improvements in muscle strength, power, and stretch-shortening cycle function compared with concentric-only or traditional resistance training. Therefore, eccentric-based training can lead to unique neuromuscular (e.g., improved coordination of motor units) and morphological (e.g., increased muscle fascicle length and enhanced distal cross-sectional area) adaptations that could play a key role in sport performance. Practitioners may implement eccentric exercises with external loads, fully eccentric-based exercises (e.g., Nordic hamstring curl), accentuated eccentric loading, flywheel resistance exercise, and plyometrics to develop specific physical adaptations in line with their goals. Eccentric work (e.g., for hamstrings) can be obtained during other exercises such as downhill running tasks, decelerations, and sprinting activities. Practitioners need to be aware that no single "silver bullet" training modality exists; consequently, practitioners should use a combination of eccentric-based training approaches with their athletes to obtain the desired adaptations.